The effects of object-oriented coupling and cohesion measures on the quality of open source systems - Awang Abu Bakar, Normi Sham (s.n, 2012)
Design metrics play an important role to help developers understand the software design aspects which later can be used to improve software quality. This paper provides empirical evidence supporting the role of object-oriented (OO)coupling and cohesion metrics, using a subset of Chidamber and Kemerer OO metrics suite, in predicting the post-delivery defects